Aplikasi E-Transaksi dan Pelaporan Kegiatan di Galeri Investasi Politeknik Piksi Ganesha - Devira Nurani Bate'e; Utami Yuditianingsih; Karyadi; Candra Mecca Sufyana (KITA Institute, 2022)
An investment gallery in a university becomes a teaching medium, especially for students in studying investment in the capital market. Transactions and processing of investor data at the Piksi Ganesha Polytechnic Investment Gallery, Bandung are currently still done manually and not yet computerized so that the recapitulation of investment activities, search for investor data, and transaction reporting and investor activity data is not yet effective and efficient, so this study aims to design transaction applications. and web-based Investor activity data reporting at the Piksi Ganesha Polytechnic Investment Gallery Bandung. The research method used is descriptive qualitative with data collection techniques through observation, interviews, documentation and literature study. The software development method uses the waterfall. Information system design using data flow diagrams and implementation with PHP programming language with bootstrap framework and My SQL database. It is hoped that the Investment Gallery application can make it easier for investors to get information and facilitate transactions and for users to make it easier to manage activities and report investment activities transactions.